The role of diffusion processes in the self-discharge of electrochemical capacitors - Hess, L. H.; Fulik, N.; Roehner, J.; Zhang, E.; Kaskel, Stefan; Brunner, Eike; Balducci, Andrea (Energy Storage Materials, 2021)
Self-discharge is a spontaneous process taking place in electrochemical double layer capacitors (EDLCs) that might affect their introduction into specific applications. In recent years, several studies investigated the dynamics of the potential decay occurring during the self-discharge of EDLCs, but the impact of diffusion processes on the self-discharge is still not well understood. In order to gain information about this important aspect we carried out a study in which we combined in situ NMR spectroscopy and electrochemical techniques. We found that the diffusion processes taking place at the electrode-electrolyte interphase are not static, as commonly assumed, but dynamically influence the self-discharge of EDLCs. These results suggest that the models describing this spontaneous process should be revised, and the diffusion should not be considered as a static, but as a dynamic process affecting self-discharge of EDLCs.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Diffusion; Electrolyte; In situ NMR; Self-discharge; Supercapacitors